Regulation of the membrane structure by brassinosteroids and progesterone in winter wheat seedlings exposed to low temperature - Filek, Maria; Rudolphi-Skórska, Elżbieta; Sieprawska, Apolonia; Kvasnica, Miroslav; Janeczko, Anna (Steroids, 2017)
Steroids constitute one of the most important groups of compounds of regulatory properties both in the animal and plant kingdom. In plants, steroids such as brassinosteroids or progesterone, by binding to protein receptors in cell membranes, regulate growth and initiate processes leading to increased tolerance to stress conditions. Due to their structural similarities to sterols, these steroids may also directly interact with cellular membranes. Our aim was to determine the changes of the structural parameters of lipid membranes under the influence of hydrophobic steroid compounds, i.e., 24-epibrassinolide (EBR) and its precursor-24-epicastasterone (ECS) and progesterone (PRO). Lipids were isolated from wheat seedlings with different tolerances to frost, grown at low temperatures (5 °C) for 1.5 and 3 weeks (acclimation process). Control plants were cultured continuously at 20 °C. From galactolipids and phospholipids, the main polar lipid fractions, the monolayers were formed, using a technique of Langmuir trough. EBR and ECS were introduced into monolayers, together with lipids, whereas the PRO was dissolved in the aqueous sub-phase upon which the monolayers were spread. Measurements performed at 25 °C and 10 °C showed a significant action of the tested compounds on the physicochemical properties of the monolayers. EBR and PRO increased the area per lipid molecule in monolayers, resulting in formation of more flexible surface structures while the presence of the ECS induced the opposite effect. The influence of the polarity of lipids and steroids on the interactions in the monolayer was discussed. Lipids extracted from the membranes of wheat with the most tolerance to frost were characterized by the highest fatty acid unsaturation and steroids had a relatively weak effect on the parameters of the structure of their monolayers.
Keywords: Lipid Metabolism; metabolismus lipidů; Cold Temperature; Progesterone; Seedlings; Brassinosteroids; nízká teplota; Cell Membrane; Triticum; Membrane Lipids; pšenice; membránové lipidy; semenáček; brassinosteroidy; buněčná membrána; progesteron